An IRF2BP member (CgIRF2BP) involved in negative regulation of CgIFNLP expression in oyster Crassostrea gigas. Issue 134 (March 2023) - Qiao, Xue; Wang, Sicong; Zong, Yanan; Gu, Xiaoyu; Jin, Yuhao; Li, Youjing; Wei, Zhuorui; Wang, Lingling; Song, Linsheng
Abstract: The IRF2BP family of transcription regulators act as corepressor molecules by inhibiting both enhancer-activated and basal transcription involving in many biological contexts. In the present study, an IRF2BP homologue ( Cg IRF2BP) was identified from oyster C. gigas . Its open reading frame is of 1809 bp encoding a polypeptide of 602 amino acids, which contains an IRF-2BP1_2 domain and a RING domain. The mRNA transcripts of Cg IRF2BP were detected in all tested tissues with highest level in haemocytes (28.99-fold of that in mantle, p < 0.05). After poly (I:C) stimulation, the expression level of Cg IRF2BP was significantly down-regulated at 3 h (0.50-fold of that in control group, p < 0.001) and gradually increased from 6 h to 48 h (2.69-fold of that in control group, p < 0.01). The recombinant protein of Cg IRF2BP (r Cg IRF2BP) showed high affinity to both r Cg IRF1 and r Cg IRF8 with Kd value of 1.02 × 10 −7 and 2.09 × 10 −7, respectively. In Cg IRF2BP-RNAi oysters, the mRNA expression of Cg IFNLP, Cg Mx1, Cg Viperin and Cg IFI44L were significantly increased after poly (I:C) stimulation, which were 2.88 ( p < 0.01), 1.83 ( p < 0.05), 2.47 ( p < 0.05), and 1.99-fold ( p < 0.01) of that in EGFP group, respectively. These findings suggested that Cg IRF2BP negatively regulated Cg IFNLP expression by binding with Cg IRF1 and Cg IRF8. Highlights: A IRF2BP homologue ( Cg IRF2BP) with conserved domain architectures was identified from oyster. Cg IRF2BP showed down-regulated expression at 3 h and then gradually increased from 6 h to 48 h after immune stimulation. Cg IRF2BP showed binding activity to Cg IRF1 and Cg IRF8 in vitro. The deficiency of Cg IRF2BP increased the expression of Cg IFNLP and Cg ISGs.